Ethics headmaster from the point of view of teachers and their relationship with some variables (A field study in Lattakia) - Barakat , Ghassan; Sbeira , Fouad; Najeeb, Enaya (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The study aimed to find out whether there was statistically significant between the average teacher answers differences with respect to the ethics of the school principal and teachers point of view due to the variable sex and years of experience and place of the school and educational qualification. The study was conducted during the academic year / 2013-2014 / on a stratified random sample of teachers of the first cycle of basic education schools in the province of Latakia reached (379) teachers, and used the resolution as a research tool prepared by the researcher, After reviewing the educational literature on the study. The study found the following results: 1. the presence of statistically significant differences in the significance level (0.05) between the average responses of teachers with regard to the ethics of the headmaster of the teachers point of view attributed to the school's location, 2. There were no statistically significant differences at the level (0.05 ) due to the variable sex, experience and qualifications, and finally I suggested several recommendations that will help managers in promoting and upgrading the moral level of their profession.